2015
DOI: 10.1590/1414-431x20144340
|View full text |Cite
|
Sign up to set email alerts
|

Vagotomy ameliorates islet morphofunction and body metabolic homeostasis in MSG-obese rats

Abstract: The parasympathetic nervous system is important for β-cell secretion and mass regulation. Here, we characterized involvement of the vagus nerve in pancreatic β-cell morphofunctional regulation and body nutrient homeostasis in 90-day-old monosodium glutamate (MSG)-obese rats. Male newborn Wistar rats received MSG (4 g/kg body weight) or saline [control (CTL) group] during the first 5 days of life. At 30 days of age, both groups of rats were submitted to sham-surgery (CTL and MSG groups) or subdiaphragmatic vago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 36 publications
6
34
0
2
Order By: Relevance
“…Studies indicate that these vagal afferents are altered in obesity, which contributes to hyperphagia [10,12]. Consistent with these findings, truncal vagotomy has been shown to reduce food consumption in rodents [19,26] and humans [17]. Conversely, high-fat diet rats did not demonstrate any alteration in food intake after vagotomy or vagal de-afferentiation [31], similarly to our observations for food consumption in CAF Vag rats.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Studies indicate that these vagal afferents are altered in obesity, which contributes to hyperphagia [10,12]. Consistent with these findings, truncal vagotomy has been shown to reduce food consumption in rodents [19,26] and humans [17]. Conversely, high-fat diet rats did not demonstrate any alteration in food intake after vagotomy or vagal de-afferentiation [31], similarly to our observations for food consumption in CAF Vag rats.…”
Section: Discussionsupporting
confidence: 91%
“…Although the pathophysiology of obesity is complex and not completely understood, several investigations using obese rodents or humans have demonstrated that the vagus nerve may contribute to obesity development and maintenance [3,4,17,19,30,31]. An increased PNS action, associated with reduced SNS activity, is implicated in fat deposition in hypothalamic, genetic, and high-fat diet-induced obesity [27,29,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations